Impact of the Audio-Visual Learning Method on the Development of Foreign Language Communication Competence of Future Interpreters and Translator - Tetiana Sobol (Educational Challenges)
This article purpose is to concern the importance of applying a communicative approach to learning a foreign language by future interpreters and translators. The communicative approach creates situations that are as close as possible to the peculiarities of the real process of communication.